2017
DOI: 10.1002/ajmg.b.32515
|View full text |Cite
|
Sign up to set email alerts
|

Associations between neurodevelopmental genes, neuroanatomy, and ultra high risk symptoms of psychosis in 22q11.2 deletion syndrome

Abstract: 22q11.2 deletion syndrome is a neurogenetic disorder resulting in the deletion of over 40 genes. Up to 40% of individuals with 22q11.2DS develop schizophrenia, though little is known about the underlying mechanisms. We hypothesized that allelic variation in functional polymorphisms in seven genes unique to the deleted region would affect lobar brain volumes, which would predict risk for psychosis in youth with 22q11.2DS. Participants included 56 individuals (30 males) with 22q11.2DS. Anatomic MR images were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 108 publications
0
12
0
5
Order By: Relevance
“…Further, genetic studies in 22q11.2DS, both in animals and humans, have found several genes within the microdeletion site that are thought to be implicated in some of the psychiatric difficulties associated with 22q11.2DS. For example, COMT and PRODH have been linked to both psychosis and ASD 34 , 35 . Although there are only a few post-mortem studies in 22q11.2DS to date, which report subtle cortical lamination defects in a 3 month old 36 , and a loss or failure to differentiate upper layer projection neurones in the cortex 37 , these appear to relatively consistent with the changes in the cortical architecture that are typically observed in Schizophrenia, and to some extent ADHD and ASD 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Further, genetic studies in 22q11.2DS, both in animals and humans, have found several genes within the microdeletion site that are thought to be implicated in some of the psychiatric difficulties associated with 22q11.2DS. For example, COMT and PRODH have been linked to both psychosis and ASD 34 , 35 . Although there are only a few post-mortem studies in 22q11.2DS to date, which report subtle cortical lamination defects in a 3 month old 36 , and a loss or failure to differentiate upper layer projection neurones in the cortex 37 , these appear to relatively consistent with the changes in the cortical architecture that are typically observed in Schizophrenia, and to some extent ADHD and ASD 33 .…”
Section: Discussionmentioning
confidence: 99%
“…The function of hZDHHC8 has been mainly characterized to date in the brain, where loss of the genomic hZDHHC8 locus in microdeletions at 22q11 is associated with cognitive deficits and schizophrenia [2426]. To our knowledge, hZDHHC8 has not been implicated in cancer so far, except that knockdown of hZDHHC8 makes mesothelioma cells more sensitive to radiotherapy [27].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, RTN4R(−/−) mice have proven to have deficits in spatial learning (Lazar et al, ) and memory task (van Gaalen, Relo, Mueller, Gross, & Mezler, ). Thompson et al () found a correlation between a specific allelic variation of this gene and reduced posterior cerebral volumes, which are thought to be responsible for some visual and social cognitive deficits of the syndrome.…”
Section: Social Cognition Relationships With Specific Phenotypes Of 2mentioning
confidence: 99%